Temperature analysis on fire resistance experiments of partially encased beams - Piloto, P.A.G. (2011)
Twelve fire resistance teslS, grouped in four series, were developed using partially encased beams (PEB) WitllOut concrete slob, for different load levei and shear connection. PEB were built witll standard bot rolled IPEJOO profile and reinforced concrete between flanges. Fire resistance was determined for standard 1S0834 nominal beating curve, using small fire resistance fumace and portal trame. Temperature was measured in Ihree differenl sections along PEB lengtll, for three differenl materiais (steel, concrete and reinforcemenl). Average temperature in each section and material was compared lo lhe average over length lemperature. Each series presented similar resuHs, wilh good reproducibility. Special focus was given to crilical temperature. The maximum temperature difference between sections SI, S2, S3 and lhe averoge elemen! lengtll temperature is smaller than 3.2% for tesl scries 1. For test series 2, 3 and 4 lhe maxirnum lemperature difference is smaller Ihan 5.1 %, 6.3% and 11.2%, respectively. Temperature is no! uniform in cross-section. Afler the ini!ial heating stag;e, temperature revealed a constan! difference ofapproximately IS0'C between temperatures measured inside and outside, defining two main temperature evolutions. Temperatures measured outside revealed a1ways higher temperature leveI.